Identification of the optical and near-infrared counterpart of GRS 1758-258 - Muñoz Arjonilla, A. J. (2010)
Context. Understood to be a microquasar in the Galactic center region, GRS 1758-258 has not yet been unambiguously identified to have an optical/near-infrared counterpart, mainly because of the high absorption and the historic lack of suitable astrometric stars, which led to the use of secondary astrometric solutions. Although it is considered with 1E 1740.7-2942 as the prototypical microquasar in the Galactic center region, the Galactic origin of both sources has not yet been confirmed. Aims. We attempt to improve previous astrometry to identify a candidate counterpart to GRS 1758-258. We present observations with the Gran Telescopio de Canarias (GTC), in which we try to detect any powerful emission lines that would infer an extragalactic origin of this source. Methods. We use modern star catalogues to reanalyze archival images of the GRS 1758-258 field in the optical and near-infrared wavelengths, and compute a new astrometric solution. We also reanalyzed archival radio data of GRS 1758-258 to determine a new and more accurate radio position. Results. Our improved astrometric solution for the GRS 1758-258 field represents a significant advancement on previous works and allows us to identify a single optical/near-infrared source, which we propose as the counterpart of GRS 1758-258. The GTC spectrum of this source is however of low signal-to-noise ratio and does not rule out a Galactic origin. Hence, new spectral observations are required to confirm or discard a Galactic nature.